Pengembangan Aplikasi Konsultasi Dokter Online Menggunakan Model SCRUM - Yulianti Yulianti; Aldianur Muhammad Herjendi; Aldy Yoga Kusuma; Dion Bagastinova; Muhamad Sahril (Jurnal Informatika Universitas Pamulang, 2022)
The Covid-19 pandemic was able to paralyze the activities of the Indonesian people in various fields of service, health, education, and the economy. Restrictions on people's activities outside the home make everything digital. The effects of this pandemic are a lot of anxiety felt by the public. And also many hospitals limit their practice hours for consultations. The Scrum method used in the development of the Online Doctor Consultation application has advantages over other development methods. Scrum can produce quality software and also save time and money. In addition, optimal use of software development time is generated. The development of an online doctor consultation application using the scrum method is carried out in 4 sprints. With sprint 1 for 62 hours, Sprint 2 for 54 hours, Sprint 3 for 72 hours, sprint for 72 hours for a total of 260 hours which can be completed in 3 months. The development of the Online Doctor Consultation application with the scrum method is very appropriate to use to reduce the company's financial expenses and can also be done with a team that is not too large. Applications generated by the scrum method are also very good. And also SCRUM can adapt to changes quickly.